(untitled) - Choi, Seok-ki (Hoboken, N.J., 2004)
For educators, graduate students, and researchers in academic and the pharmaceutical industry, Choi, himself a chemist in the industry, describes the molecules, which are now accepted as an effective strategy for designing ligands, inhibitors, and drugs that influence biological systems potently and selectively. He begins by reviewing multivalent interactions in biological systems and the role in them of both natural and synthetic multivalent molecules. Then he looks at the design concept, synthesis, and biological activity of molecules designed to target viruses, bacteria, and mammalian-cells. He closes by summarizing various aspects of synthetic methods used to synthesize multivalent molecules, including combinatorial approaches developed in library design
Keywords: Multivalent molecules,Multivalent molecules,Multivalent molecules; Synthesis.,Design,Physiological effect